A Framework for Traceable and Transparent Supply Chain Management for Agri-food Sector in Malaysia using Blockchain Technology - Chan, Kok Yong; Johari, Abdullah; Adnan Shahid, Khan (The Science and Information (SAI) Organization Ltd., 2019)
This paper presents a framework for traceable and transparent supply chain management (SCM) system for the agri-food sector using blockchain technology in Malaysia. Numerous researchers believed that the current SCM system consists of several weak points, especially when multiple enterprise resource planning (ERP) system utilizing centralized SCM. Thus, data transparency and traceability are limited. This study hypothesized that if blockchain technology correlates with transparency and traceability of SCM, the above limitation can be minimized, as blockchain technology works in a distributed manner. This research uses “pepper” as an agri-food domain. The research also recommends that permissioned blockchain is a better fit as compared to permissionless blockchain.